Development and Evaluation of an AI-Powered MRCPsych CASC Simulator for Exam Preparation - Sirous Golchinheydari (BJPsych Open)
Aims: Preparation for the MRCPsych CASC exam can present unique challenges for psychiatry trainees, including limited access to structured practice, real-time feedback and standardized patient interactions. This project aimed to develop the MRCPsych CASC Simulator (MCS), a custom AI-powered tool designed to enhance exam preparation by providing interactive clinical simulations, structured feedback and objective performance assessment.